Peningkatan Efisiensi Produksi Briket Batok Kelapa Menggunakan Mesin Cetak Kapasitas 10kg - Baiti Hidayati; M. Rasid; Herlin Sumarna; Romli Romli; Aji Pangestu Wijaya (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Manual production of coconut shell briquettes in small and medium-scale industries often faces limitations in productivity, product uniformity, and dependence on human labor. This study aimed to evaluate the efficiency improvement of coconut shell briquette production through the use of a 10 kg-capacity briquetting machine. An experimental method was applied by comparing mechanical briquetting and manual hand-pressing using the same raw material composition, namely 7 kg of coconut shell charcoal powder, 3 kg of tapioca starch adhesive, and 1 liter of water as a mixing aid. The observed parameters included production capacity, production time, physical quality score, quality consistency, and electrical energy consumption. The results showed that the machine produced 10 kg of briquettes in 1 hour, whereas the manual method produced approximately 3.3 kg per hour and required about 3 hours to reach the same production quantity. The machine increased production capacity by approximately 200% and reduced production time by approximately 67%. The physical quality score increased from 70% to 85%, while quality consistency increased from 80% to 95%. Although the machine consumed 0.5 kWh per process, the energy requirement was relatively low, equivalent to 0.05 kWh/kg of briquettes. These findings indicate that the 10 kg-capacity briquetting machine is feasible as an appropriate technology to improve productivity and product uniformity for small and medium-scale coconut shell briquette producers.